Salts and cocrystals of furosemide with pyridines: differences in π-Stacking and color polymorphism - Sangtani, Ekta; Mandal, Suman Kumar; Sreelakshmi, A. S.; Munshi, Parthapratim; Gonnade, Rajesh G. (Crystal Growth & Design, 2017)
Furosemide (FS), a loop diuretic drug that has a potential to exhibit polymorphism, produced color polymorphs of orange (form 1I) and yellow (form 1II) concomitantly with coformer 1, 2-bis(4-pyridyl)ethylene. However, cocrystallization of FS with other pyridines yielded colorless salts (2 and 4) and cocrystals (3 and 5). The significant color difference between the two polymorphs (forms 1I and 1II) could be attributed to the dissimilar π-stacking patterns between the two components and differences in their highest occupied molecular orbital−lowest unoccupied molecular orbital gap. The molecular packing of form 1I and 2 is very similar, but 2 is colorless due to lack of extended π-conjugation.